Determinants Influencing Banking Practices among Municipal Residents - Rana, Bikash (Devkota Journal of Interdisciplinary Studies, 2023)
Sustaining financial stability and managing family finances require the application of sound banking practices. Finding the important variables that affect city dwellers’ banking preferences is the main goal of this study. The research was conducted in the Rupandehi District of Nepal, specifically located in the Lumbini Zone within the Western Development Region, specifically within the Tilottama Municipality. A diverse range of individuals, encompassing various age groups, genders, occupations, and educational backgrounds, actively participated in the study by diligently completing comprehensive questionnaire. Using a mix of descriptive and causal research frameworks, the study found that factors like convenience, and security have a positive influence on banking behaviors. Conversely, no meaningful relationship was found between the urban population’s banking practices and awareness, availability and motivational factors. The similarity of bank services and the greater levels of financial awareness and literacy that are common in cities may be the cause of this lack of correlation. Therefore, the results of this study may be helpful to banking institutions in creating and putting into practice plans to boost banking participation.